Synthesis and Characterization of A[W2O2F9] (A = Li – Cs). Issue 23 (28th May 2020) - Stene, Riane E.; Scheibe, Benjamin; Karttunen, Antti J.; Petry, Winfried; Kraus, Florian
Abstract : Herein, we report upon the in situ formation of WOF4 and its subsequent reaction with A F ( A = Li – Cs) in aHF to produce A [W2 O2 F9 ] ( A = Li – Cs). Structural analysis of the obtained compounds was performed using single‐crystal X‐ray diffraction. A comparison of the single‐crystal structures obtained here to the previously reported A [Mo2 O2 F9 ] ( A = Li – Cs) and H3 O[W2 O2 F9 ] salts is given. Additionally, IR and Raman spectroscopy were used to characterize each salt. These spectra were compared to calculated ones for the solid‐state structure of each salt using the DFT‐PBE0 density functional method. The calculated spectra were used to assign bands in the experimental spectra. Both MoOF4 and WOF4 gave similar reaction products under similar reaction conditions. It was concluded that the oxyfluorides show similar Lewis acid‐base reactions with the alkali metal fluorides in aHF solutions. Abstract : The Lewis acid‐base reaction of WOF4 with the alkali metal fluorides in anhydrous hydrogen fluoride solution was studied. A series of salts having the general formula A [W2 O2 F9 ] ( A = Li – Cs) resulted. Each salt was characterized by single‐crystal and powder X‐ray diffraction, and by IR and Raman spectroscopy. Vibrational spectra were interpreted with the help of quantum chemical methods.